VARIASI SINTAKSIS BAHASA INGGRIS PARA GURU BAHASA INGGRIS DI KOTA PADANG, SUMATERA BARAT (Universitas PGRI Sumatera Barat, 2017)
English has become a language spread all over the world. The sociolinguistic facts show that various variations of English arise due to local language and cultural contact. In the context of English language learning in a country that uses English as a foreign language, it is still believed that English teachers in schools teach standard English namely British Received Pronunciation and Standard American English. However, this condition needs to be questioned whether the English teachers actually use standard English or whether they use a certain English variation. The purpose of this study is to describe the English language used by teachers in syntax. Several English teachers who taught in high school in Padang became participants in this study. The results of this study show that the English teachers have a syntactic difference with the English standard English and British English. The results of this study can provide information on teaching English in Indonesia.